Tinjauan Hukum Mengenai Transaksi Afiliasi dan Benturan Kepentingan pada Perusahaan Terbuka dalam Studi Kasus PANI dan CBDK - Tiwi Ayu Haresa Dewi; Nayla Aliffia; Riksya Annurillah; Alexandra Vandela Putri; Adeliya Putri (Media Hukum Indonesia (MHI), 2026)
Public companies frequently engage in related-party transactions, particularly business groups with ownership and control ties. However, if such transactions are not conducted transparently and fairly, they can lead to conflicts of interest. The objective of this study is to examine the legal provisions related to related-party transactions and conflicts of interest arising in the relationship between PT Pantai Indah Kapuk Dua Tbk (PANI) and PT Bangun Kosambi Sukses Tbk (CBDK), as well as efforts to prevent them. The research method used is normative legal research with a statutory approach and a case study approach. The results of the study indicate that transactions between PANI and CBDK constitute affiliated transactions subject to Financial Services Authority Regulation No. 42/POJK.04/2020. This regulation specifically governs information disclosure, the use of independent appraisers, and the approval of independent shareholders in the event of a conflict of interest. Corporate management, internal controls, the principle of fairness, and legal due diligence can all help prevent conflicts of interest. Therefore, compliance with regulations is crucial to ensuring that corporate transactions in the Indonesian capital market remain valid.